Infantile Fibrosarcoma and Other Spindle Cell Neoplasms of Infancy. A Review of Morphologically Overlapping yet Molecularly Distinctive Entities. (2nd November 2022) - Jabbari, Shiva; Salari, Behzad; He, Mai; Dehner, Louis P.
Abstract: Background: Regardless of age at presentation, many soft tissue neoplasms have overlapping histopathologic and immunophenotypic features to serve as a diagnostic challenge. Case report: We reported a case of a spindle cell neoplasm in an infant, which was initially considered a vascular anomaly clinically and an eventual biopsy revealed marked inflammation with a spindle cell component that was resolved as an infantile fibrosarcoma with an ETV6 break-apart. Conclusion: The context of this case lead to a further consideration of various other spindle cell neoplasms arising predominantly in the soft tissues during the infancy period as defined by the first two years of age. Though sharing similar morphologic features, these tumors can be categorized into several molecular genetic groups, which have provided both diagnostic and pathogenetic insights as well as treatment options in some cases.